Cancer survivors' experiences of discharge from hospital follow-up - Harrison, SE; Watson, E; Ward, A; Khan, N; Turner, D; Adams, E; Forman, D; Roche, M; Rose, P (2012)
Discharge from hospital follow-up is a key time point in the cancer journey. With recommendations for earlier discharge of cancer survivors, attention to the discharge process is likely to become increasingly important. This study explored cancer survivors' experiences of discharge from hospital follow-up. Survivors of breast, colorectal and prostate cancer (n= 1275), 5-16 years post diagnosis were approached to take part in a questionnaire survey. The questionnaire included questions about discharge status, provision of time/information prior to discharge, feelings at discharge and satisfaction with how discharge was managed. Completed questionnaires were returned by 659 survivors (51.7%). Approximately one-third of respondents were not discharged from follow-up 5-16 years post diagnosis. Of those discharged, a substantial minority reported insufficient time (27.9%), information (24.5-45.0%) or adverse emotions (30.9%) at the time of discharge. However, 90.6% of respondents reported satisfaction with how discharge from hospital follow-up was managed. Despite high levels of satisfaction, discharge of cancer survivors from hospital follow-up could be improved with the provision of additional time, information and support. Better structuring of the final hospital appointment or a review appointment in primary care at this time could help to ensure that discharge from hospital follow-up is managed optimally for cancer survivors. © 2011 Blackwell Publishing Ltd.